2003
DOI: 10.1046/j.1365-294x.2003.01988.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and habitat partitioning of genetically distinct zooxanthellae (Symbiodinium) in Acropora corals on the Great Barrier Reef

Abstract: Intra- and intercolony diversity and distribution of zooxanthellae in acroporid corals is largely uncharted. In this study, two molecular methods were applied to determine the distribution of zooxanthellae in the branching corals Acropora tenuis and A. valida at several reef locations in the central section of the Great Barrier Reef. Sun-exposed and shaded parts of all colonies were examined. Single-stranded conformational polymorphism analysis showed that individual colonies of A. tenuis at two locations harb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
164
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(171 citation statements)
references
References 28 publications
5
164
1
1
Order By: Relevance
“…Nevertheless, this scenario should be corroborated by studying more coral species co-occurring in the same environment before a firm conclusion can be stated. Recent studies have taken the further step of suggesting that Phylotype D is a heat-tolerant Symbiodi- *PCR amplifications were unsuccessful due to the poor quality of the DNA extraction nium (Glynn et al 2001, Baker 2003a,b, 2004, Ulstrup & van Oppen 2003, Fabricius et al 2004, Little et al 2004, Rowan 2004. Glynn et al (2001) showed that Far-Eastern Pacific corals hosting Phylotype D symbionts had suffered less from the 1998 coral bleaching event than those coral associated with other symbiont phylotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this scenario should be corroborated by studying more coral species co-occurring in the same environment before a firm conclusion can be stated. Recent studies have taken the further step of suggesting that Phylotype D is a heat-tolerant Symbiodi- *PCR amplifications were unsuccessful due to the poor quality of the DNA extraction nium (Glynn et al 2001, Baker 2003a,b, 2004, Ulstrup & van Oppen 2003, Fabricius et al 2004, Little et al 2004, Rowan 2004. Glynn et al (2001) showed that Far-Eastern Pacific corals hosting Phylotype D symbionts had suffered less from the 1998 coral bleaching event than those coral associated with other symbiont phylotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Since, type D zooxanthellae did exist in some of the Keppel corals and was not evident in the Davies population, even after a long period of transplantation and despite bleaching, the change is likely to have been a shuffling of existing zooxanthella types. Low background levels of zooxanthella type D (as low as ca 0.001%) have been detected using quantitative PCR methods in C-dominated Acropora valida corals on the GBR (Ulstrup & van Oppen 2003), suggesting that this strategy is potentially available to other coral populations and species. However, the fact that Davies transplants did not change symbiont type suggests that symbiont switching may only take place under certain conditions.…”
Section: Keppels Top a C G T A C C G C G T T Keppels Bottommentioning
confidence: 99%
“…Clade C-and clade D-specific ITS1 primer pairs were obtained from Ulstrup and van Oppen (2003) (Table 2). A 25 ll real-time PCR reaction contained: 1· IQ SYBR Green supermix (BioRAD), 180 nM clade Symbiodiniumuniversal forward primer, 180 nM clade C-or D-specific reverse primer and 2.5 ll coral DNA template (MilliQ H 2 O in case of no-template controls).…”
Section: The Real-time Pcr Assaymentioning
confidence: 99%